Women's entrepreneurship in the 21st century an international multi-level research analysis - edited by Kate V. Lewis (Cheltenham UK Edward Elgar Publishing, 2014)
This volume takes a multi-dimensional approach to the central theme of gender and entrepreneurship today and in the future. It takes a holistic approach to exploring, via empirical and theoretical lenses, why women's involvement in venture creation matters.
Includes bibliographical references and index.
Keywords: Businesswomen